2020
DOI: 10.7717/peerj.9764
|View full text |Cite
|
Sign up to set email alerts
|

Projection range of eDNA analysis in marshes: a suggestion from the Siberian salamander (Salamandrella keyserlingii) inhabiting the Kushiro marsh, Japan

Abstract: Background Freshwater ecosystems are rapidly declining. The Siberian salamander (Salamandrella keyserlingii) which inhabits the Kushiro marsh in Hokkaido, Japan has lost some habitat due to human activity. There are many challenges associated with conventional monitoring methods, including cost, the need for specialist personnel, environmental impact, and ability to detect the presence of this species; thus, we investigated the feasibility of using environmental DNA (eDNA) analysis to detect its presence and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
(49 reference statements)
2
5
0
Order By: Relevance
“…Our study showed spikes in mu‐ and nu‐eDNA concentrations after artificial fertilization (0 hpf) and after most of the embryos finished hatching (96 hpf). This was consistent with Takeshita et al (2020), who found concentrated eDNA emissions just after spawning and hatching, and limited emissions during the incubation phase in the egg sacs of the Siberian salamander ( Salamandrella keyserlingii ) in tank experiments. This suggests that the spikes in eDNA concentration during a breeding season in aquatic species may be used to monitor and understand the spawning and hatching events.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study showed spikes in mu‐ and nu‐eDNA concentrations after artificial fertilization (0 hpf) and after most of the embryos finished hatching (96 hpf). This was consistent with Takeshita et al (2020), who found concentrated eDNA emissions just after spawning and hatching, and limited emissions during the incubation phase in the egg sacs of the Siberian salamander ( Salamandrella keyserlingii ) in tank experiments. This suggests that the spikes in eDNA concentration during a breeding season in aquatic species may be used to monitor and understand the spawning and hatching events.…”
Section: Discussionsupporting
confidence: 92%
“…This suggests that the spikes in eDNA concentration during a breeding season in aquatic species may be used to monitor and understand the spawning and hatching events. Takeshita et al (2020) determined that the eDNA results from the field could reflect the number of egg sacs in the sampling sites within breeding habitats. Our study also revealed a positive relationship between the number of hatched individuals and the eDNA concentrations of Cytb and ITS1, suggesting that the eDNA copy numbers during embryo development may potentially be used to estimate the relative number of hatched larvae.…”
Section: Discussionmentioning
confidence: 99%
“…High DNA concentrations were also found in some tanks immediately after the eggs hatched (Sample ID = 4). Although it is difficult to make a simple comparison because of the difference in taxonomic groups, some studies have reported increased eDNA concentrations after hatching of eggs [ 38 ]. In contrast, when focusing on the persistence of eDNA, eDNA was detected until at least seven days after the emergence and departure of all adult mosquitoes.…”
Section: Discussionmentioning
confidence: 99%
“…Such eDNA signals would be useful for evaluating mosquito habitats. Although it is di cult to make a simple comparison because of the difference in taxonomic groups, some studies reported increased eDNA concentrations after eggs hatched [29]. However, eDNA is rarely detected during the egg period.…”
Section: Discussionmentioning
confidence: 99%